On The extension Bi-Normality of Linear Operators - Hijab , Anas A.; Abdulwahid, Elaf S. (Iraqi Journal of Science, 2023)
In this paper, we introduce the bi-normality set, denoted by , which is an extension of the normality set, denoted by for any operators in the Banach algebra . Furthermore, we show some interesting properties and remarkable results. Finally, we prove that it is not invariant via some transpose linear operators.